ANALISIS PERENCANAAN PERSEDIAAN BAHAN BAKU (STUDY KASUS PD. GUNUNG MAS JAMBI) - Ahmad Firdaus (Universitas Batanghari Jambi, 2008)
This research entitle analysis of soy bean row material inventory planning of PD. Gunung Mas Jambi. The objective of this research is to look at wether the company could reach it’s planning or not.In analizing the data the writer uses the cuantitative descriptive method, that the data is described in numeral form and then, be analized and be concluded.The result of the research bring the writer to the conclution that PD. Gunung Mas Jambi has never reached 100% of the planning. The problem is caused by the row materials are cut off. So PD. Gunung Mas Jambi should correct the activity of the planning. Key Words : Inventory, Row Material and Planning